Systematic review and meta-analysis of birth weight and prenatal exposure to perfluoroundecanoic acid - Hongyu Ru; Paige A. Bommarito; Michael W. Dzierlenga; Alexandra L. Lee; Kristen M. Rappazzo; Benjamin J.K. Davis; Avanti V. Shirke; Alexis Agbai; Elizabeth G. Radke; Thomas F. Bateson; J. Michael Wright (Environmental Research, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Organ-specific off-target effects of Pim/ZIP kinase inhibitors suggest lack of contractile Pim kinase activity in prostate, bladder, and vascular smooth muscle - Sheng Hu; Moritz Trieb; Ru Huang; Alexander Tamalunas; Patrick Keller; Melanie Götz; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Smooth muscle contraction by Pim kinases and ZIPK has been suggested, but evidence for lower urinary tract organs or using Pim-selective inhibitor concentrations is not yet available. Here, we assessed effects of the Pim inhibitors AZD1208 and TCS PIM-1 and the dual ZIPK/Pim inhibitor HS38 on contractions of human prostate and bladder tissues and of porcine interlobar arteries. Human tissues were obtained from radical prostatectomy and radical cystectomy and renal interlobar arteries from pigs. Contractions were studied in an organ bath. Noradrenaline-, phenylephrine- and methoxamine-induced contractions were reduced (up to > 50%) with 500-nM AZD1208 in prostate tissues and to lesser degree and not consistently with all agonists in interlobar arteries. A total of 100-nM AZD1208 or 500-nM TCS PIM-1 did not affect agonist-induced contractions in prostate tissues. Decreases in agonist-induced contractions with 3-µM HS38 in prostate tissues and interlobar arteries were of small extent and did not occur with each agonist. Carbachol-induced contractions in detrusor tissues were unchanged with AZD1208 (500 nM) or HS38. Electric field stimulation–induced contractions were not affected with AZD1208 or HS38 in any tissue, but slightly reduced with 500-nM TCS PIM-1 in prostate tissues. Concentration-dependent effects of Pim inhibitors suggest lacking Pim-driven smooth muscle contraction in the prostate, bladder, and interlobar arteries but point to organ-specific functions of off-targets. Procontractile functions of ZIPK in the prostate and interlobar arteries may be limited and are lacking in the detrusor.

Upcycling soybean pulp for sustainable amino acid and subsequent protein biomanufacturing via a one-pot thermophilic protease cascade treatment - Ronnie G. Gicana; Min-Hsuan Huang; Tony Z. Jia; Yin-Ru Chiang; Po-Hsiang Wang (Chemical Engineering Journal, 2023)

Valorization of soybean pulp for sustainable α-ketoisocaproate production using engineered Bacillus subtilis whole-cell biocatalyst - Eugene Huang; Jhen-Sheng Yan; Ronnie G. Gicana; Yin-Ru Chiang; Fang-I Yeh; Chieh-Chen Huang; Po-Hsiang Wang (Chemosphere, 2023)

When things get MESI: The Manipulation Experiments Synthesis Initiative—A coordinated effort to synthesize terrestrial global change experiments - Kevin Van Sundert; Sebastian Leuzinger; Martin K.‐F. Bader; Scott X. Chang; Martin G. De Kauwe; Jeffrey S. Dukes; J. Adam Langley; Zilong Ma; Bertold Mariën; Simon Reynaert; Jingyi Ru; Jian Song; et al. (Global Change Biology, 2023)
Responses of the terrestrial biosphere to rapidly changing environmental conditions are a major source of uncertainty in climate projections. In an effort to reduce this uncertainty, a wide range of global change experiments have been conducted that mimic future conditions in terrestrial ecosystems, manipulating CO 2 , temperature, and nutrient and water availability. Syntheses of results across experiments provide a more general sense of ecosystem responses to global change, and help to discern the influence of background conditions such as climate and vegetation type in determining global change responses. Several independent syntheses of published data have yielded distinct databases for specific objectives. Such parallel, uncoordinated initiatives carry the risk of producing redundant data collection efforts and have led to contrasting outcomes without clarifying the underlying reason for divergence. These problems could be avoided by creating a publicly available, updatable, curated database. Here, we report on a global effort to collect and curate 57,089 treatment responses across 3644 manipulation experiments at 1145 sites, simulating elevated CO 2 , warming, nutrient addition, and precipitation changes. In the resulting Manipulation Experiments Synthesis Initiative (MESI) database, effects of experimental global change drivers on carbon and nutrient cycles are included, as well as ancillary data such as background climate, vegetation type, treatment magnitude, duration, and, unique to our database, measured soil properties. Our analysis of the database indicates that most experiments are short term (one or few growing seasons), conducted in the USA, Europe, or China, and that the most abundantly reported variable is aboveground biomass. We provide the most comprehensive multifactor global change database to date, enabling the research community to tackle open research questions, vital to global policymaking. The MESI database, freely accessible at doi.org/10.5281/zenodo.7153253 , opens new avenues for model evaluation and synthesis‐based understanding of how global change affects terrestrial biomes. We welcome contributions to the database on GitHub.

COSEν: A collective oscillation simulation engine for neutrinos - Manu George; Chun-Yu Lin; Meng-Ru Wu; Tony G. Liu; Zewei Xiong (Computer Physics Communications, 2023)

Vibrational Characterization and Molecular Electronic Investigations of 2-acetyl-5-methylfuran using FT-IR, FT-Raman, UV–VIS, NMR, and DFT Methods - Victoria M. Bassey; Chioma G. Apebende; Precious S. Idante; Hitler Louis; Wilfred Emori; Chun-Ru Cheng; John A. Agwupuye; Tomsmith O. Unimuke; Kun Wei; Fredrick C. Asogwa (Journal of Fluorescence, 2022)

Inhibition of neurogenic contractions in renal arteries and of cholinergic contractions in coronary arteries by the presumed inhibitor of ADP-ribosylation factor 6, NAV2729 - Ru Huang; Bingsheng Li; Alexander Tamalunas; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
NAV2729 is a presumed inhibitor of the monomeric GTPase ADP ribosylation factor 6 (ARF6) and inhibits smooth muscle contraction outside the cardiovascular system. Its effects on vascular smooth muscle contraction or a possible role of ARF6 in vasocontraction have not yet been examined. Here, we report effects of NAV2729 on neurogenic and agonist-induced contractions in renal interlobar and coronary arteries. Contractions of pig interlobar and coronary arteries were induced in an organ bath by agonists or by electric field stimulation (EFS). Owing to divergent characteristics of both vessel types, EFS-induced contractions were only examined in interlobar arteries, and contractions by agonists acting on muscarinic receptors only in coronary arteries. NAV2729 inhibited frequency-dependent EFS-induced contractions of interlobar arteries. The degree of inhibition was similar using 5 µM and 10 µM NAV2729. Inhibition of EFS-induced contractions was resistant to a nitric oxide synthase inhibitor and to diclofenac. The neurogenic and adrenergic character of EFS-induced contractions was confirmed by inhibition by tetrodotoxin and prazosin. In coronary arteries, NAV2729 (5 µM) inhibited concentration-dependent contractions induced by carbachol and methacholine. Contractions induced by α 1 -adrenergic agonists, endothelin-1, the thromboxane receptor agonist U46619, or serotonin remained unchanged by NAV2729 in both vessel types. NAV2729 inhibits neurogenic contractions in interlobar arteries and contractions induced by cholinergic agonists in coronary arteries. In both vessel types, NAV2729 does not inhibit contractions induced by receptor agonists other than those acting on muscarinic receptors. Addressing effects in other vessels and in other smooth muscle–rich organs merits further attention.

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

Purinergic smooth muscle contractions in the human prostate: estimation of relevance and characterization of different agonists - Annabel Spek; Bingsheng Li; Beata Rutz; Anna Ciotkowska; Ru Huang; Yuhan Liu; Ruixiao Wang; Frank Strittmatter; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Non-adrenergic prostate smooth muscle contractions may account for the limited effectiveness of α 1 -adrenoceptor antagonists, which are the first-line option for medical treatment of voiding symptoms suggestive of benign prostatic hyperplasia. In non-human prostates, purinergic agonists induce contractions reaching similar magnitudes as α 1 -adrenergic contractions. However, evidence for the human prostate is highly limited, and pointed to much weaker purinergic contractions. Here, we examined contractions of different purinergic agonists in human prostate tissues. Tissues were obtained from radical prostatectomy. Contractions were studied in an organ bath, and expression of purinergic receptors was studied by RT-PCR. Electric field stimulation (EFS)–induced contractions amounted to 104% of KCl-induced contractions (95% CI: 84–124%). From all tested agonists, only ATP induced concentration-dependent contractions, reaching an average maximum of 18% (12–24%) of KCl. Maximum tensions following application of other agonists averaged to 7.1% of KCl for α,β-methylene-ATP (1.8–12.4%), 3.9% for β,γ-methylene-ATP (2.0–5.4%), 3.1% for 2-methylthio-ATP (− 0.1–6.3%), and 5.1% for ATPγS (1.0–9.2%). Responses were not affected by the P2X antagonist NF023 or the P2Y antagonist PPADS. mRNA expression of P2X1-4 correlated with expression of a marker for catecholaminergic nerves, although neither ATP, NF023, nor PPADS changed EFS-induced contractions. Correlation between expression of receptors and the smooth muscle marker calponin was not observed. Our findings point to a low relevance of purinergic contractions in the human prostate, compared to other contractile stimuli in the human prostate and compared to purinergic contractions in non-human prostates. Purinergic contractions in the human prostate are not sensitive to NF023 or PPADS.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genome-wide association study for flour color-related traits and polyphenol oxidase activity in common wheat - X.L. Jiang; G.F. Chen; X.J. Li; G. Li; Z.G. Ru; J.C. Tian (Cereal Research Communications, 2018)

Repeated Neonatal Sevoflurane Exposure-Induced Developmental Delays of Parvalbumin Interneurons and Cognitive Impairments Are Reversed by Environmental Enrichment - Mu-huo Ji; Zhong-yun Wang; Xiao-ru Sun; Hui Tang; Hui Zhang; Min Jia; Li-li Qiu; Guang-fen Zhang; Yong G. Peng; Jian-jun Yang (Molecular Neurobiology, 2017)

Raman spectra of polycrystalline microdiamond inclusions in zircons, and ultrahigh-pressure metamorphism of a quartzofeldspathic rock from the Erzgebirge terrane, Germany - Ru Y. Zhang; Juhn G. Liou; Ching-Hua Lo (International Geology Review, 2017)

Identification of a novel wheat- Thinopyrum ponticum addition line revealed with cytology, SSR, EST-SSR, EST-STS and PLUG markers - X. J. Li; X. G. Hu; T. Z. Hu; G. Li; Z. G. Ru; L. L. Zhang; Y. M. Lang (Cereal Research Communications, 2015)

The role of slow and fast protein motions in allosteric interactions - Shiou-Ru Tzeng; Charalampos G. Kalodimos (Biophysical Reviews, 2015)

Serological and virological survey of hepatitis E virus in wild boar populations in northwestern Italy: detection of HEV subtypes 3e and 3f - Claudio Caruso; P. Modesto; S. Bertolini; S. Peletto; P. L. Acutis; A. Dondo; S. Robetto; W. Mignone; R. Orusa; G. Ru; L. Masoero (Archives of Virology, 2015)

Association of a specific major histocompatibility complex class IIβ single nucleotide polymorphism with resistance to lactococcosis in rainbow trout, O ncorhynchus mykiss (Walbaum) - S Colussi; M Prearo; S A Bertuzzi; T Scanzio; S Peletto; L Favaro; P Modesto; M G Maniaci; G Ru; R Desiato; P L Acutis (Journal of Fish Diseases, 2015)
Major histocompatibility complex ( MHC ) loci encode glycoproteins that bind to foreign peptides and initiate immune responses through their interaction with T cells. MHC class II molecules are heterodimers consisting of α and β chains encoded by extremely variable genes; variation in exon 2 is responsible for the majority of observed polymorphisms, mostly concentrated in the codons specifying the peptide‐binding region. L actococcus garvieae is the causative agent of lactococcosis, a warm‐water bacterial infection pathogenic for cultured freshwater and marine fish. It causes considerable economic losses, limiting the profitability and development of fish industries in general and the intensive production of rainbow trout, O ncorhynchus mykiss (Walbaum), in particular. The disease is currently controlled with vaccines and antibiotics; however, vaccines have short‐term efficacy, and increasing concerns regarding antibiotic residues have called for alternative strategies. To explore the involvement of the MHC class II β‐1 domain as a candidate gene for resistance to lactococcosis, we exposed 400 rainbow trout to naturally contaminated water. One single nucleotide polymorphism ( SNP ) and one haplotype were associated with resistance ( P MHC class IIβ as a molecular marker in breeding rainbow trout resistant to lactococcosis.

Phylogeography in continuous space: coupling species distribution models and circuit theory to assess the effect of contiguous migration at different climatic periods on genetic differentiation in B usseola fusca ( L epidoptera: N octuidae) - S. Dupas; B. le Ru; A. Branca; N. Faure; G. Gigot; P. Campagne; M. Sezonlin; R. Ndemah; G. Ong'amo; P.‐A. Calatayud; J.‐F. Silvain (Molecular Ecology, 2014)
Current population genetic models fail to cope with genetic differentiation for species with large, contiguous and heterogeneous distribution. We show that in such a case, genetic differentiation can be predicted at equilibrium by circuit theory, where conductance corresponds to abundance in species distribution models ( SDM s). Circuit‐ SDM approach was used for the phylogeographic study of the lepidopteran cereal stemborer B usseola fusca F üller ( N octuidae) across sub‐ S aharan A frica. Species abundance was surveyed across its distribution range. SDM s were optimized and selected by cross‐validation. Relationship between observed matrices of genetic differentiation between individuals, and between matrices of resistance distance was assessed through Mantel tests and redundancy discriminant analyses ( RDA s). A total of 628 individuals from 130 localities in 17 countries were genotyped at seven microsatellite loci. Six population clusters were found based on a B ayesian analysis. The eastern margin of D ahomey gap between E ast and W est A frica was the main factor of genetic differentiation. The SDM projections at present, last interglacial and last glacial maximum periods were used for the estimation of circuit resistance between locations of genotyped individuals. For all periods of time, when using either all individuals or only E ast A frican individuals, partial M antel r and RDA conditioning on geographic distance were found significant. Under future projections (year 2080), partial r and RDA significance were different. From this study, it is concluded that analytical solutions provided by circuit theory are useful for the evolutionary management of populations and for phylogeographic analysis when coalescence times are not accessible by approximate B ayesian simulations.

Unique peptide-binding motif for Mamu-B*037:01: an MHC class I allele common to Indian and Chinese rhesus macaques - Natasja G. de Groot; Corrine M. C. Heijmans; Arnoud H. de Ru; Chopie Hassan; Nel Otting; Gaby G. M. Doxiadis; Frits Koning; Peter A. van Veelen; Ronald E. Bontrop (Immunogenetics, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

Composition of stem borer communities in selected vegetation mosaics in Kenya - G. O. Ong’amo; B. P. Le Ru; P.-A. Calatayud; J.-F. Silvain (Arthropod-Plant Interactions, 2013)

Characterization and molecular mapping of RsrR, a resistant gene to maize head smut - W. H. Li; X. D. Xu; G. Li; L. Q. Guo; S. W. Wu; Y. Jiang; H. Y. Dong; M. L. Weng; D. M. Jin; J. Y. Wu; Z. G. Ru; B. Wang (Euphytica, 2012)
Maize head smut (MHS) caused by the fungi Sporisorium reilianum (Kühn) Landon and Fullerton ( S. reilianum ) is the most serious disease occurred in China recently. There are only a few reports concerning the genetics of this disease and the resistant gene of maize. In this paper a new dominant resistant gene to MHS caused by the pathogen Shenyang-1 of S. reilianum was discovered from a newly developed resistant inbred line ‘R24’ and was named RsrR. RsrR gene was molecular tagged and mapped on the long arm of maize chromosome 1 via simple sequence repeat-bulked segregant analysis (SSR-BSA) and sequence related amplified polymorphism (SRAP)-BSA analysis, the nearest linkage marker is 2.5 cM apart from the RsrR gene. The gene RsrR has been transferred into two elite maize inbred lines, ‘Huangzao4’ and ‘Qi319’, through traditional hybridization and marker assisted selection. The converted lines can be used in maize MHS-resistance breeding.

A global view of the OCA2-HERC2 region and pigmentation - Michael P. Donnelly; Peristera Paschou; Elena Grigorenko; David Gurwitz; Csaba Barta; Ru-Band Lu; Olga V. Zhukova; Jong-Jin Kim; Marcello Siniscalco; Maria New; Hui Li; Sylvester L. B. Kajuna; et al. (Human Genetics, 2012)

An AEM study of garnet clinopyroxenite from the Sulu ultrahigh-pressure terrane: formation mechanisms of oriented ilmenite, spinel, magnetite, amphibole and garnet inclusions in clinopyroxene - Shyh-Lung Hwang; Tzen-Fu Yui; Hao-Tsu Chu; Pouyan Shen; Ru-Yuan Zhang; Juhn G. Liou (Contributions to Mineralogy and Petrology, 2011)

HSPVdb—the Human Short Peptide Variation Database for improved mass spectrometry-based detection of polymorphic HLA-ligands - Harm Nijveen; Michel G. D. Kester; Chopie Hassan; Aurélie Viars; Arnoud H. de Ru; Machiel de Jager; J. H. Fred Falkenburg; Jack A. M. Leunissen; Peter A. van Veelen (Immunogenetics, 2011)

Toxicity of pesticides to Tamarixia radiata, a parasitoid of the Asian citrus psyllid - David G. Hall; Ru Nguyen (BioControl, 2010)

Phylogeography of Larix sukaczewii Dyl. and Larix sibirica L. inferred from nucleotide variation of nuclear genes - Neyton H. T. Araki; Ismael A. Khatab; Kariyawasam K. G. U. Hemamali; Nobuyuki Inomata; Xiao-Ru Wang; Alfred E. Szmidt (Tree Genetics & Genomes, 2008)

PrPSc deposition in nervous tissues without lymphoid tissue involvement is frequently found in ARQ/ARQ Sarda breed sheep preclinically affected with natural scrapie - C. Ligios; M. G. Cancedda; L. Madau; C. Santucciu; C. Maestrale; U. Agrimi; G. Ru; G. Di Guardo (Archives of Virology, 2006)

Detection of Pathological Prion Protein in the Tongue of Sheep Infected with Naturally Occurring Scrapie - C. Corona; C. Casalone; P. L. Acutis; M. I. Crescio; F. Martucci; B. Iulini; C. L. Florio; P. Gazzuola; G. Perfetti; C. Bona; G. Ru; M. Caramelli (Veterinary Research Communications, 2006)

Kokchetavite: a new potassium-feldspar polymorph from the Kokchetav ultrahigh-pressure terrane - Shyh-Lung Hwang; Pouyan Shen; Hao-Tsu Chu; Tzen-Fu Yui; Juhn G. Liou; Nikolay V. Sobolev; Ru-Yuan Zhang; Vladislav S. Shatsky; Anton A. Zayachkovsky (Contributions to Mineralogy and Petrology, 2004)

Genetic analysis, molecular tagging and mapping of the thermo-sensitive genic male-sterile gene (wtms1) in wheat - Q. H. Xing; Z. G. Ru; C. J. Zhou; X. Xue; C. Y. Liang; D. E. Yang; D. M. Jin; B. Wang (Theoretical and Applied Genetics, 2003)

Contribution to the taxonomy and phylogeny of Sarcocapnos DC. (Fumariaceae) - M. J. Salinas; C. Ruz-Rejn; C. Morales; M. Ruz-Rejn; A. T. Romero; G. Blanca; R. de la Herrn; M. Garrido-Ramos; V. Surez (Plant Systematics and Evolution, 2003)

The Role of CEA (Center of Animal Encephalopathies) in the BSE Surveillance: BSE in Italy - M. Caramelli; P. Acutis; E. Bozzetta; C. Casalone; C. Gagna; F. Ingravalle; G. Ru (Veterinary Research Communications, 2003)